A distributed implementation of an adaptive finite element method for fluid problems - De Santiago, Eduardo; Law, Kincho H. (Computers & structures, 2000)
The potential for using a network of workstations for solving the incompressible Navier–Stokes equations using the finite element method is investigated. A programming paradigm suitable for a heterogeneous distributed workstation environment is presented and compared to the traditional paradigm employed for distributed memory parallel computers. In particular, the issues of load balancing and fault recovery are explored. Extension of the programming paradigms to include mesh adaptivity is discussed.